Comparison of Increased Knowledge and Existence of Larvae between Before and After Education in Primary School Guards in Mojokerto City - Anindita Abigail; Sulistiawati Sulistiawati; Erwin Astha Triyono (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2019)
Introduction: Dengue fever is a tropical disease caused by Dengue virus that is still becoming one of the main health problem in Indonesia. Dengue fever patients are usually children with age ranging between 5-14 years old, that indicates a higher likelihood of infection at school compared to infection at home.The purpose of this study is to analyze the difference between knowledge and practice of DHF prevention and also the existence of larvae before and after education to the elementary school’s guard in MojokertoMethods:  The research method used in this study is pre-experimental design method, which is a one group pretest and posttest study.The number of samples was 25 school guards from all elementary school in the urban villages with DHF cases in 2017.Results: The average correct answer at pretest was 58.9% while in posttest it was 80.9%. From the results of Wilcoxon test also obtained p-value 0.00 (<0.05). From observation before the education, one school was found positive with larvae, and after the education was given, all schools were found negative.Conclusion: There are differences in knowledge and practice prevention of dengue fever between before and after education in primary school guards in Mojokerto